UDAN POTIR: SIMBOLIK EKOLOGIS GORDANG SAMBILAN DAN LINGKUNGAN ALAM - Ibnu Avena Matondang (Lakon : Jurnal Kajian Sastra dan Budaya, 2013)
Discourse correlation of human life with nature (ecological) became the focus of attention at the present time, the phenomenon of reduced energy and role imbalance between the supply and use of natural production to accompany thegrowing issue of human relationships with nature. Culturally, people have been living with the results provided by nature, human knowledge of nature has been summarized in the cultural record with human life from simple forms tothe complexity of life today, the use of natural products in the form of the material to the term that refers to the relationship between humans and nature recorded in the cognitive culture. This study discusses about the ecologicalspace of symbolic images that depict human relationships in a Batak-Mandailing culture with nature, the natural role that determines the attitude and behavior of people in the running life. Forms of ecological relationship between humans and nature are represented in the form of Gordang Sambilan musical repertoire.